2016
DOI: 10.1007/s00018-016-2221-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome maintenance in the context of 4D chromatin condensation

Abstract: The eukaryotic genome is packaged in the three-dimensional nuclear space by forming loops, domains and compartments in a hierarchical manner. However, when duplicated genomes prepare for segregation, mitotic cells eliminate topologically associating domains and abandon the compartmentalized structure. Alongside chromatin architecture reorganization during the transition from interphase to mitosis, cells halt most DNA-templated processes such as transcription and repair. The intrinsically condensed chromatin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 180 publications
0
13
0
6
Order By: Relevance
“…The nucleosome functions as the first level of genomic impaction, where a chain of nucleosomes forming chromatin fibres (through the interaction of their tails with adjacent nucleosomes and other proteins) which assemble into higher order three-dimensional nuclear space in a hierarchical manner (forming loops and domains), ultimately assembling chromosomes [ 6 , 7 , 8 ] ( Figure 1 B–C).…”
Section: The Role Of Nucleosomes In Packaging Dnamentioning
confidence: 99%
“…The nucleosome functions as the first level of genomic impaction, where a chain of nucleosomes forming chromatin fibres (through the interaction of their tails with adjacent nucleosomes and other proteins) which assemble into higher order three-dimensional nuclear space in a hierarchical manner (forming loops and domains), ultimately assembling chromosomes [ 6 , 7 , 8 ] ( Figure 1 B–C).…”
Section: The Role Of Nucleosomes In Packaging Dnamentioning
confidence: 99%
“…S1B), many of which result in truncated mutants lacking Cterminal PTEN (5,10). Although plasma membrane-localized PTEN function is central to suppression of the PI3K/AKT pathway, recent studies have indicated that PTEN has PI3K/AKT-independent tumor-suppressor functions (11). Cells without functional PTEN display increased chromosome instability with a high frequency of DNA double-strand breaks (DSB), suggesting that its nuclear function acts as a caretaker of the genome (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] PTEN targets phosphatidylinositol-3,4,5-triphosphate (PIP3) and antagonizes the major survival pathway regulated by phosphatidylinositol 3-kinase (PI3K)/Akt. [5][6][7] Increasing evidence indicates that nuclear PTEN has fundamental functions in maintenance of chromosomal stability, 2,[8][9][10][11][12][13][14] suggesting there are as yet unidentified mechanisms in the process of chromosome inheritance for which the function of PTEN is indispensable. It has been shown that PTEN plays an essential role in maintaining the structural integrity of individual chromosomes, 2 which supports recognition of PTEN as a guardian of the genome.…”
Section: Introductionmentioning
confidence: 99%